The effect of physical activity level towards motivation among secondary school students and implications on pre-service teacher education / Azlan Ahmad Kamal ... [et al.] - Ahmad Kamal, Azlan; Azizy, Mohamed Nor Safi; Narasuman, Suthagar; Ab Rahman, Zarizi; Zainal Abidin, Amirul Naqiq (Universiti Teknologi MARA, 2024)
The modern framework for education should be viable in defining the complex relationships between physical activity and motivation among secondary school students. The study aims to determine how physical activity level influences motivation among secondary school students. This study aims to address the implications of physical activities on youngsters' motivation from the standpoint of an educational institution. Moreover, it strives to determine motivation levels through physical activity, compare the differences between male and female students' motivation levels, and identify correlations between secondary school students' motivations. Thus, this study adopts the quantitative approach in its research design using the random questionnaire sampling technique to determine secondary school students' activity levels and motivation. The results reflected a positive correlation between physical activity and motivation among secondary school learners and that higher physical activities lead to higher motivation among the students. The research also revealed differences in physical activity levels between male and female students. However, the detailed nature of these differences is yet to be explored. Another aspect highlighted is that a dynamic interaction may occur between physical activity and motivation, whereby student involvement in the exercise might promote their level of motivation or otherwise. The results of this study can be applied by educators, policymakers, and health professionals in practical educational settings to enhance motivation and engagement among secondary school students in several ways.